Combination of sunlight with hydrogen peroxide generated at a modified reticulated vitreous carbon for drinking water disinfection. (10th April 2020) - Jin, Yanchao; Shi, Yijun; Chen, Ziyu; Chen, Riyao; Chen, Xiao; Zheng, Xi; Liu, Yaoxing
Abstract: Long treatment times limit the application of solar disinfection (SODIS). The concentrations of electrolytes in drinking water are low, so it is difficult to generate a sufficient quantity of H2 O2 for drinking water disinfection via electrochemical reduction. In this study, SODIS and electrochemical reduction were combined together. A reticulated vitreous carbon (RVC) cathode was anodised to improve its performance and characterized using scanning electron microscopy and X-ray photoelectron spectroscopy. The contributions of the electrochemical process and SODIS to disinfection were studied. The influences of current, temperature and humic acid (HA) were also investigated. The results showed that the modification of RVC added oxygen-bearing functional groups and doubled the quantity of H2 O2 generated at the cathode. When the hybrid process was employed to remove E. coli from water, The E. coli count was reduced from approximately 10 6  colony-forming units (CFUs) per mL to below the detection threshold (<4 CFU/mL) after 120 min. The disinfection time of the hybrid method was lower than those of SODIS and electrochemical disinfection alone by 60% and 20%, respectively. Increasing the current reduced the treatment time from 150 to 90 min, although the treatment consumed more electricity. HA in a low concentration (1 mg/L) could enhance the disinfection process. However, a relatively high HA concentration (4 mg/L) suppressed the inactivation of E. coli . Increasing the temperature from 20 to 40 °C reduced the treatment time from 120 to 90 min, and the electricity consumption per log of E. coli decreased from 102.2 to 64 Wh/m 3 . This study demonstrates that combining SODIS and H2 O2 electrogeneration is an effective and energy-efficient disinfection strategy. Highlights: Disinfection rate was increased by combining hydrogen peroxide with sunlight. The influence of humic acid on disinfection was determined. Raising temperature reduced the treatment time and the electricity consumption. The electricity consumption for per log E. coli removal was 102.2 Wh/m 3 at 20 °C.